Shi’ite in Malaysia: A study of their theology, rites and political inclination based on sects - Fadzli, Adam; Rahimah, Embong; Mohd Afandi, Salleh; Basri, Ibrahim; Mohd Safri, Ali; Syed Hadzrullathfi, Syed Omar (Serials Publications, 2017)
The conflict and in some ocassions clash of faith between Shi’ite and Sunni has a very long history in Islamic civilization. The expansion of Shi’ite into Sunnite-based-countries including Malaysia has become serious and alarming due to the increase of its followers. Data provided by Media Muslim.com announced that there are 154-200 millions Shi’ite followers worldwide whereas Malaysian Department of Islamic Development claimed a total number of 1000 to 1500 of Shi’ite followers. The existence of Shi’ite in different typology of sects in Malaysia has caused objection since it practices Sunni doctrine as its Islamic mainstream. Therefore, this article attempts to highlight typology of Shi’ite sects in Malaysia which differs to each other in terms of theology, rites and political inclination. Different typology of Shi’ite doctrines will be discussed at length using document analysis and interviews with selected key informants. The result of the study shows that reports by the Department of Islamic Affairs from majority states in Malaysia and information gathered from selected key informants that there are three main sects of Shi’ite in Malaysia namely Dawoodi Bohra, the Ismai’li Agha Khan and the Twelver. It is also found that each sect has its own doctrine in relation to theology, rites and political inclination which in some areas are similar to each other and in some other ocassions are different. It is expected that the finding of this study will set as indicators of different Shi’ite typology in Malaysia.